2014
DOI: 10.1021/jm500943z
|View full text |Cite
|
Sign up to set email alerts
|

Converting Potent Indeno[1,2-b]indole Inhibitors of Protein Kinase CK2 into Selective Inhibitors of the Breast Cancer Resistance Protein ABCG2

Abstract: A series of indeno[1,2-b]indole-9,10-dione derivatives were synthesized as human casein kinase II (CK2) inhibitors. The most potent inhibitors contained a N(5)-isopropyl substituent on the C-ring. The same series of compounds was found to also inhibit the breast cancer resistance protein ABCG2 but with totally different structure-activity relationships: a N(5)-phenethyl substituent was critical, and additional hydrophobic substituents at position 7 or 8 of the D-ring or a methoxy at phenethyl position ortho or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 55 publications
4
57
2
Order By: Relevance
“…It was firstly discovered in a process involving in multidrug resistance (MDR) from doxorubicin-resistant human MCF-7 breast cancer cells [46], and was also reported to induce sorafenib resistance in hepatocellular carcinoma (HCC) cells [7]. Further investigation indicated that ABCG2 is over-expressed in various tumor cells [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…It was firstly discovered in a process involving in multidrug resistance (MDR) from doxorubicin-resistant human MCF-7 breast cancer cells [46], and was also reported to induce sorafenib resistance in hepatocellular carcinoma (HCC) cells [7]. Further investigation indicated that ABCG2 is over-expressed in various tumor cells [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis procedure, as well as the analytical data, are given in the supporting information. In contrast, the following ten compounds used for the training and test sets, namely 4e, 4f, 4g, 4v, 4x, 4y, 5d, 5j, 5k, and 6g, which have been published before [16,17,35]. The inhibitory activity of all used indeno [1,2-b]indoles was tested on recombinant human CK2 and the inhibition results are shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…All indeno[1,2-b]indole derivatives 1-30 used in this study were synthesized by us. The procedures for the synthesis of indeno [1,2-b]indoles have already been described for compounds 4e [35], 4f [35], 4g [17], 4v [35], 4x [16], 4y [16], 5d [17], 5j [16], 5k [16], and 6g [16]. For the compounds 4d, 4h-j, 4p-s, 4w, 5a, 5c, 5f, 5h, 5g, and 6a-f, the chemistry is described in the Supporting Information (Files S1 and S2).…”
Section: Chemistrymentioning
confidence: 99%
“…Table 1. Structures of the ketonic indeno [1,2-b]indoles and their IC50 values towards CK2, which were used for the training and test sets, data from Alchab et al [9] and Gozzi et al [13]. MOE software (Chemical Computing Group, Montreal, Canada) package was used to perform this study [21].…”
Section: Resultsmentioning
confidence: 99%